Correlation of the Areal Number Density of Vascular Bundles with the Mechanical Properties of Oil Palm Wood (Elaeis guineensis Jacq.) - Rattana Choowang (Masyarakat Peneliti Kayu Indonesia, 2018)
Currently most of oil palm trunks in Thailand are left on the field to rot or are burnt in the field, not utilized as lumber. To promote such value-added uses, the objective of this study was to characterize the levels and variation within oil palm trunks of their key mechanical properties. In addition, the vascular bundle population was assessed, because this structural characteristic affected density and mechanical properties. The key ones being here were modulus of rupture (MOR), modulus of elasticity (MOE), and hardness. The 25 years old oil palm trunks were selected from a palm plantation in Surat Thani Province, in southern Thailand. The trees were cut down at 500 mm above ground, cut into dices, then sawn into small pieces in radial direction. Vascular bundle populations and basic densities were determined. Oil palm lumber was sawn from the logs between wood dices, and their mechanical properties were determined. The results indicated that the vascular bundle population density gradually decreased towards the central axis of trunks, and the population density positively correlated with basic density and mechanical properties. This was because the main component of a vascular bundle has fibers with thick cell walls. The data obtained may help select or create products that match the properties of oil palm wood (Elaeis guineensis Jacq.), or contributed to the sorting of wood raw material based on, for example, machine vision.